The Impact of Bariatric Surgery on Men's Reproductive Health: Hormonal, Semen, and Fertility Outcomes - Nicknama, Reza; Karimi, Khatoon; Abedi, Amir Reza; Samenezhad, Sina (Archives of Men's Health, 2025)
Background: Obesity has a growing global prevalence and is closely associated with impaired male reproductive health, including hormonal imbalances and subfertility. Bariatric surgery is the most effective intervention for sustained weight loss in morbidly obese individuals, but its impact on reproductive outcomes in men remains unclear. Methods: We performed a narrative review of studies published between 2005 and 2025 that examined the effects of bariatric surgery on hormonal profiles, semen quality, and fertility outcomes in men. Literature was identified through PubMed, with additional targeted searches in Embase and Cochrane. Studies were included if they evaluated male reproductive parameters before and after bariatric surgery. Results: Evidence consistently demonstrates significant increases in testosterone levels post-surgery. However, semen quality outcomes are variable, with some studies showing improvements in sperm motility and morphology, while others report reductions in semen volume and concentration, particularly after malabsorptive procedures. Data on fertility outcomes, including in vitro fertilization (IVF) success rates, are limited and based on small sample sizes. Nutritional deficiencies are a frequent complication and may contribute to negative reproductive outcomes. Conclusion: Bariatric surgery restores hormonal balance in obese men but has heterogeneous effects on semen parameters and fertility. Long-term, large-scale studies are needed to clarify reproductive risks and optimize perioperative fertility care.